2005
DOI: 10.1021/ol052684r
|View full text |Cite
|
Sign up to set email alerts
|

Facile Preparation and Reactivity of Polymer-Supported N-(2-Iodyl-phenyl)-acylamide, an Efficient Oxidizing System

Abstract: A simple three-step preparation of polymer-supported N-(2-iodyl-phenyl)-acylamide (NIPA resin) starting from 2-iodoaniline is described. The resin was obtained with good loading levels (0.7-0.8 mmol g(-1)) and has been successfully used for efficient oxidation of a diverse collection of alcohols. Thus, treating alcohols with 1.0 equiv of the resin in 1,2-dichloroethane under reflux for 30-60 min allowed rapid and in most cases complete conversion to the corresponding carbonyl compound.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 21 publications
0
28
0
Order By: Relevance
“…Based on the remarkable acceleration of the oxidation of phenols by addition of only a small amount of iodoarene and documented examples of the reactions of iodoarene and Oxone ® , which produce pentavalent iodine species, [43][44][45][46][47][48] it was suggested that iodine(V) species, generated in situ, was included in this oxidation as the active catalyst. However, formation of pentavalent iodine species requires a higher temperature (70°C) than that in the oxidation of 2 with 1a and Oxone ® .…”
Section: Resultsmentioning
confidence: 99%
“…Based on the remarkable acceleration of the oxidation of phenols by addition of only a small amount of iodoarene and documented examples of the reactions of iodoarene and Oxone ® , which produce pentavalent iodine species, [43][44][45][46][47][48] it was suggested that iodine(V) species, generated in situ, was included in this oxidation as the active catalyst. However, formation of pentavalent iodine species requires a higher temperature (70°C) than that in the oxidation of 2 with 1a and Oxone ® .…”
Section: Resultsmentioning
confidence: 99%
“…For biologically active compounds containing the acylamide system, see: Bennasar et al (2006); Ladziata et al (2006). For bond-length data, see: Gao et al (2007).…”
Section: Related Literaturementioning
confidence: 99%
“…To avoid the supplementary preparation of tetrabutylammonium oxone, we have examined the oxidation of the polymer 41 in a dichloromethane/water biphasic system using oxone, tetrabutylammonium hydrogen sulfate and methanesulfonic acid. 20 The synthesis employs commercially available aminomethylated polystyrene, includes three simple steps, and affords the resin with good loading (0.70-0.80 mmol·g -1 ). These loading levels are comparable with the values reported for IBX amide resin (0.65-0.98 mmol·g -1 ).…”
Section: Polymer-supported N-(2-iodylphenyl)acylamide (Nipa Resin)mentioning
confidence: 99%
“…20 Most alcohols were oxidized to the respective aldehyde or ketone products in excellent purities and yields. As one exception, oxidation of 3-(pyridin-2-yl)propan-1-ol (Table 2, entry 20) led to the formation of a black tar, presumably due to the instability of pyridinylpropanal towards heating.…”
Section: Polymer-supported N-(2-iodylphenyl)acylamide (Nipa Resin)mentioning
confidence: 99%